Assessing the UV protection levels of selected standard-issued delivery riders’ uniforms and specialized UV protective clothing a comparative analysis - Rullan, Anna Cecilia C.
Prolonged exposure to ultraviolet (UV) radiation poses significant health risks, especially for individuals frequently working outdoors, such as motorcycle delivery riders. This study assessed the UV protection levels of selected standard-issued motorcycle delivery uniforms compared to specialized UV-protective clothing. The research responds to growing global and local concerns regarding occupational sun exposure, especially in tropical countries like the Philippines, where outdoor workers are especially vulnerable. The study assessed and compared the Ultraviolet Protection Factor (UPF) ratings of three standard-issued uniforms and one UV-protective clothing based on their fabric characteristics, including fiber composition, fabric construction, weight, and density. A descriptive comparative research design was employed. Samples were purposively selected and laboratory-tested at the Philippine Textile Research Institute (DOST-PTRI). Data were collected through standardized UPF testing methods (AATCC TM183-2020e), and fabric properties were tested using relevant ASTM test standards. Results revealed that while two standard-issued uniforms achieved “Very Good” UPF classifications, one was rated only “Good.” In contrast, the specialized UV-protective clothing achieved an “Excellent” UPF rating, providing greater protection than the uniform samples. This suggests that current uniform standards do not offer sufficient UV protection for outdoor workers since none reach the UPF 50+ rating, which is the required UPF rating to qualify for The Skin Cancer Foundation’s Seal of Recommendation. The study recommends integrating improved uniform design and UV-certified clothing into occupational clothing standards and promoting awareness of UV protection among employers and workers to ensure long-term skin health and safety.